STRATEGI GURU PADA PENANGANAN SISWA DISLEKSIA DI SEKOLAH DASAR - Imam Nurcahyo Ika Putra; Novi Anita Puteri Ramadhani; Mumtahanah Wanodiasari; Minsih Minsih (Satya Widya)
This study aims to explore the strategies employed by teachers in addressing the needs of students with dyslexia in elementary schools. Specifically, the research seeks to gain an in-depth understanding of the approaches utilized by teachers at SD Negeri 03 Karangbangun when supporting dyslexic students. Data collection methods included observation, interviews, documentation, and data processing aligned with the research focus. To ensure data validity, triangulation techniques were employed by comparing findings from observations and interviews. Data analysis was conducted interactively. The participants involved were fourth- and fifth-grade teachers, as well as a fifth-grade student with dyslexia. The findings of this study indicate that the strategies used by teachers to support dyslexic students in elementary schools include: (1) providing individualized assistance through extended learning time focused on activities such as spelling, reading, and writing; and (2) utilizing information technology-based tools, such as Word Wall or engaging instructional videos, to create a supportive and stimulating learning environment for dyslexic students.